Analisis Losses Inti/Kernel pada Cangkang Light Tenera Dry Separator (LTDS) No.1 Menggunakan Metode Statistical Process Control (SPC) pada PT. Socfindo Kebun Sei Liput Aceh Tamiang - Ryan Pramanda; Alifya Ghina Syahra (Journal of Electrical Engineering, 2026)
This study aimed to analyze kernel losses in the shell fraction of Light Tenera Dry Separator (LTDS) No. 1 at PT Socfindo Sei Liput Estate using the Statistical Process Control (SPC) method. Data were collected through direct observation of the kernel and shell separation process and analyzed using control charts to evaluate process stability. The results showed that the blower inverter frequency ranged from 50.38 to 56.45 Hz, while kernel losses varied between 0.60% and 0.98%. These values remained below the company's maximum allowable limit of 1%, indicating that the separation process was under control. However, kernel losses were still affected by several factors, including improper blower frequency settings, uneven kernel cracking at the ripple mill, and unstable material flow during the separation process. Therefore, regular monitoring of operating parameters and routine maintenance of the LTDS are necessary to maintain optimal machine performance and minimize kernel losses, thereby improving the overall efficiency of the production process